«ШАРЬЯР» ДӘСТАНЫНДА РУЎХЫЙ-ӘДЕП-ИКРАМЛЫЛЫҚ ТӘРБИЯСЫ МӘСЕЛЕЛЕРИ - Алламбергенов, Е.К. (ILIM hám JÁMIYET, 2019)
The article is devoted to one of the actual issues of history and theory of Pedagogy. The issues of spiritual-educational upbringing were analyzed on the basis of the materials from an epos «Shariyar». In the result of the research the author comes to the conclusion that the epos «Shariyar» is not only the valuable literary heritage of folklore, but it is considered to be an effective and powerful means of education.